ANALISIS TEMBOK PENAHAN (REVETMENT) HULU BENGAWAN SOLO - , AROMAN KARSENSYAH S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Revetment works is additional work contained in the contract addendum II. The work of revetment added to follow up on previous spillway work that has been accomplished spillway. Revetment is intended to allow the river wall is not eroded, especially on the 15- RP.L19 RP.L block. Therefore, careful planning is required in order to obtain an economical revetment plans, strong and easy implementation. Revetment plans made after measuring the location of the project (using the Total Station) and checking soil classification (using sondir). Once the data is processed, then revetment. planning is carried out in accordance field conditions. Revetment plans refers to JIS (Japan International standarts) as the main guideline. Revetment use lean against type of revetment, using class E concrete for structures, and concrete class F for floor work. The dimensions are used in accordance with the plan (1 block = 10 meters). Reinforcement bar used is D16-125.